Enhancing Financial Performance through Supply Chain Innovation (SCI) with mediating role of Robustness and Resilience Capability in Thailand’s manufacturing sector - Thammarak Srimarut; Witthaya Mekhum (International Journal of Supply Chain Management, 2020)
Purpose: Main objective of this research is to assess the relation between SCI and risk management capabilities of firms and to focus that how innovation and risk affect financial performance. Methodology: In order to analyze the hypotheses developed in this study, survey method in the form of questionnaire was adopted to collect data from the manufacturing firms of Thailand. The data collected in then analyzed by using different statistical tools including SPSS and AMOS. Findings: Outcomes of research clearly shows that SCI has significant positive impact on the level of risk associated with firms including both robust and resilience risk factors in terms of technological advancements. The results show that these variables are inter-related with each other which means that with the increase in innovativeness, the risk associated with it also increases as a result the financial performance of firms also increases. Implications: The research provides data and an addition in literature related to SC management by investigating the impact of innovation on risk and performance levels of firms. It also provides help to mangers to critically analyze and to make sound decisions related to impacts of technological processes on their Supply chain (SC) practices globally. Novelty: This study is unique in its own perspective because it has focused on the relationship of SC innovation, risk management as well as financial performance altogether of the manufacturing firms that are involved in international levels of SC in Thailand.